Three Pillars Approach as Gender Perspective and Poverty Alleviation Model - S, Rosalia Indriyati; Nugrahani, Tri Siwi; Rejeki, Sri (Jurnal Penelitian Kesejahteraan Sosial, 2018)
The purpose of this research are to conduct an inventory of village poverty problems, describe the actual conditions of rural women poverty map, analyze the poverty alleviation programs with a gender perspective, as well as an overview of coordination between relevant agencies poverty alleviation programs, formulate policy design strategy model of poverty reduction through socio-cultural approach and economics. This research is qualitative approach. Data are collected through observation, documentation, and depth interview. Research subjects are officials and community members of poverty alleviation programs. It can be revealed that the numbers of poor households in Sleman Regency are 45.037 families (13.89 persen). Various poverty alleviation programs have been conducted by various work units, but the synergy among units in the poverty eradication program not yet works, although the target data used program has been one source. Programs among agencies run their own because they often work in sectoral programs. The results of the research can be summarized as follows: Sleman district government strongly supports reduction gender perspective model, since there is a gender disparity in Sleman, which can be seen from index of 79.29 persen, gender development index 75.76 persen and gender inequality gap 3.65 persen. This is due to the access to better education school are male dominated; Access to capital strengthening male-dominated, women still lack of access. Poverty alleviation models with a gender perspective can be tested in Sleman, and will be a pioneer for women with access to poverty reduction. The results of the questionnaire showed that the stage in the design of the model is expressed well, and the meaning of each stage is considered good. Thus, the model of a gender perspective in poverty reduction strategies can be tested.